Ron, Osvaldo; Cachorro, Gabriel y Ferrety, Emmanuel (coords.) (2017) Cuerpo, arte y Comunicación - Santalla, Lucia (2018)
Fil: Fil: Santalla, Lucia. Instituto Superior de Educación Física Nº 11 "Abanderado Mariano Grandoli"; Argentina.